Kajian Prespektif Layananan Digital Library - Yusniah Yusniah; Nur Syahada Sinaga; Novita Sari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Information system is an information technology and activities for those who use it to support management activities. A digital library is an organization that provides information resources, including librarians, to select, organize, provide access, translate, distribute, maintain unity, and maintain the continuity of digital collections so that users can always access them and use them easily. Digital libraries offer services as well as information centers. Digital library services are those that are available digitally through computer networks and the internet. The purpose of this study is to explain the current digital library phenomenon and the services provided by outlining the challenges and opportunities they face. This study uses a literature review research method. Literature review is more often referred to as a literature review in the field of research, especially the creation of scientific works. Therefore, literature review can be described as an analytical activity that can be in the form of criticism of a particular scientific work related research projects in the field. Explanation or discussion of the theory of a finding or research topic is the content of this literature review. The explanation of these theories can be used as a theoretical basis for scientific work or research. The result of this study is that digital libraries differ from local copies in terms of storage and physical location. From the start, most of the work done by digital libraries was centralized and organized like a regular library. Digital libraries are influenced by the human resources and infrastructure they have used to provide services. Libraries must meet the needs of their customers. Human resources or librarians who also follow the development of information technology are very important for information-providing libraries. Therefore, it is hoped that librarians will be able to meet customer needs through the provision of superior digital services.